Ozark Country - Rayburn, Otto Ernest (Book collections on Project MUSE., 2021)
"Chronicles of the Ozarks reissue of Otto Ernest Rayburn's 1941 Ozark Country. Edited and with a new introduction by Ozarks scholar Brooks Blevins"--